Jenis-jenis Gastropoda di Zona Intertidal Pantai Amor-amor Kabupaten Lombok Utara - Sucika Armiani; Baiq Muli Harisanti; Titi Laily Hajiriah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Gastropods have an important ecological role in coastal ecosystems, such as decomposing organic matter, playing an important role in the food chain and with the characteristics of the habitat at the bottom of the substrate, this organism is used as a bioindicator to assess the quality of the marine environment. The importance of initial documentation of the types of marine biota in an area needs to be done, one of which is on Amor-amor Beach where this area is the center of the development of aquaculture activities in the North Lombok area. This study aims to identify the types of gastropods in the intertidal zone of Amor-Amor Beach, North Lombok Regency. This type of research is descriptive exploratory. The study was conducted in July - September 2024. Sampling by purposive sampling consisted of three stations, namely; station 1 (waters facing the Tambak inlet), station 2 (waters in the outlet area) and station 3 (waters far from the tambak area). The sampling used a 1x1 m transect, species attached to rocks were taken directly, while species that burrowed or were in the sand substrate were taken by placing a PVC pipe frame with a sieve. Species of unknown type were put into a sample bottle given a 70% alcohol solution, then identified using an identification book and several internet literature. The results of this study found 23 species of gastropods from 13 families, namely the Neritidae family (4 species), the Muricidae family (2 species), the Conidae family (5 species), the Nassaridae family (4 species), the Strombidae family (2 species) and 1 species for each of the Collumbelidae, Olividae, Littorinidae, Cypraeidae, Ranelidae, Nacelidae, Turbinidae, and Trochidae families. This finding is important as a basis for information for biodiversity conservation efforts and as an ecological indicator in coastal environmental biomonitoring activities.